Pomen vključevanja staršev v vzgojno-izobraževalni proces šole - Kovač, Jernej (Revija za elementarno izobraževanje, 2009)
The importance of including parents in the educational process. The relationship between schools and parents is one of the key factors for the educational success of a chi Id. Thus some scientific statements that deal with problems in the relationship between school (teachers) and parents are shown in the article. This is the main reason we wanted to show the importance of cooperation between schools and parents, which is based on trust, mutual respect, consideration of one another, consideration of individuality and forms of cooperation. It is an opportunity for parents to actively cooperate with schools. Later in the article we describe the negative and positive factors that can influence the relationship between schools and parents. The end of the article describes plans for improving the relationship be-tween schools and parents, which are based on constant support of teachers, professional training and other forms of education.